Optimizing ground station networks for free space optical communications: Maximizing the data transfer. Issue 2 (26th October 2018) - Capelle, Mikaël; Huguet, Marie‐José; Jozefowiez, Nicolas; Olive, Xavier
Abstract: Free space optical communications are becoming a mature technology to cope with the needs of high data rate payloads for future low‐earth orbiting observation satellites. However, they are strongly impacted by clouds. In this paper, we aim to find a network of optical ground stations maximizing the percentage of data acquired by a low‐earth orbiting satellite that can be transferred to the Earth, taking into consideration cloud information. This problem can be separated in two parts and solved hierarchically: the selection of a network of optical ground stations and the assignment of downloads to visibility windows of the stations. We present theoretical and practical results regarding the complexity of the latter subproblem and propose a dynamic programming algorithm to solve it. We combine this algorithm with two methods for the enumeration of the stations, and compare them with a mixed integer linear program (MILP). Results show that even if the MILP can solve scenarios over small horizons, the hierarchical approaches outperform it in term of computation time while still achieving optimality for larger instances.